Saint and Nation : Santiago, Teresa of Avila, and Plural Identities in Early Modern Spain - Rowe, Erin Kathleen, 1974- (Book collections on Project MUSE., 2011)
"Examines the controversy in early seventeenth-century Spain over the elevation of Saint Teresa of Avila to co-patron saint alongside the traditional patron, Santiago. Assesses the crucial role of sanctity in the symbolic representation of the nation in early modern Europe"--